RIRS with FV-UAS vs. ESWL for the management of 1–2 cm lower pole renal calculi in obese patients: a prospective study - Men, Chao; Xu, Miao; Zhang, Si-cong; Wang, Qing; Wu, Jie; Li, Yun-Peng (Frontiers in Medicine, 2024)
Objective To evaluate the efficacy and safety of retrograde intrarenal surgery (RIRS) combined with flexible vacuum-assisted ureteral access sheath (FV-UAS) versus extracorporeal shock wave lithotripsy (ESWL) for the management of 1–2 cm lower pole renal calculi (LPC) in obese patients. Patients and methods This prospective, randomized study included 149 obese patients with 1–2 cm LPC. Patients were allocated into two groups: 76 patients underwent RIRS with FV-UAS, and 73 patients received ESWL. The parameters assessed included stone-free rate (SFR), retreatment rate, complications, operative time, and pain intensity measured by the visual analog scale (VAS). Stone-free status was defined as the absence of stones on computed tomography or residual fragments smaller than 4 mm at 4 weeks post-procedure. Results The baseline characteristics of the two groups were comparable. The SFR was significantly higher in the RIRS group, reaching 86.8%, compared to 63.0% in the ESWL group (p = 0.034). Furthermore, the retreatment rate was significantly lower in the RIRS group, at 5.2%, versus 24.7% in the ESWL group (p < 0.001). The average operative time for RIRS was notably longer, at 65.3 ± 6.4 min, compared to 25.3 ± 7.8 min for ESWL (p < 0.001). The complication rates were 9.2% for the RIRS group and 6.8% for the ESWL group, with no statistically significant difference (p = 0.326). All complications were classified as Grade I or II according to the modified Clavien classification system. No significant differences were observed between the two groups regarding pain VAS scores and the composition of the stones. Conclusion RIRS with FV-UAS demonstrated superior efficacy, evidenced by a higher SFR and reduced retreatment rates compared to ESWL, despite a longer operative duration. Both treatment modalities showed comparable safety profiles. RIRS with FV-UAS emerges as a viable, effective, and reproducible intervention for managing 1–2 cm LPC in obese patients, providing significant clinical advantages.